PENERAPAN PEMBELAJARAN BERDASARKAN MASALAH MATERI BILANGAN BERPANGKAT DAN LOGARITMA - Suhartono Suhartono; Hery Setiyawan (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2018)
This research is conducted to describe students’ activities during the implementation of problem-based learning in the topic of exponential number and logarithm and management of problem-based learning exponential number and logarithm by lecturer This research is a descrptive research, that is a research which has aim to describe research’s variables qualitatively and quantitatively. The topic that is used in this research is exponential number and logarithm. Subject of this research is students in PGSD Program, University of ijaya Kusuma Surabaya. Instrument of this research is observation sheet of students’ activities and observation sheet of the organising of problem-based learning by lecturer. The students’ activities and the organising of problem-based learning by the lecturer are collected as data. The data is analised descriptively. The result of this research shows that the students’activities and the effectivity are excellent. The result of this research also shows that the effectivity of the lecturer is good. Based on the result of this research, teachers or lecturers may apply this problem-based learning to make the learning process in class effective.